PENGARUH SUMBER DANA PIHAK KETIGA, NON PERFORMING LOAN DAN RETURN ON ASSET TERHADAP PROFIT GROWTH BANK KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Handayani,, Anik; Lusiyanti, Lina (JURNAL EKONOMI PEMBANGUNAN, 2023)
This study aims to determine the effect of Third Party Fund Sources (DPK), Non-Performing Loans (NPL) and Return on Assets (ROA) on profit growth of banks listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. This research uses a Quantitative type of research with a descriptive approach. The object of this study are bank listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The population used in this study was 20 banks and using this sampling technique was carried out using purpose sampling. There are two data analysis techniques used, namely multiple linear regression analysis and simple regression. The results and conclusions of this study show that partially Third Party Funds (DPK) has a positive effect on the Return on Assets (ROA) of banks listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period, Non-Performing Loans (NPL) have no effect on banking Return on Assets (ROA) and Return on Assets (ROA) has a positive effect on the growth of banking profits listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 periode.